EMPOWERMENT AND TRANSFORMATIONAL LEADERSHIP BEHAVIORS AND EMPLOYEE WELL-BEING: THE MEDIATING ROLE OF ORGANIZATIONAL SUPPORT - Sara T. Msuya (Journal of Applied Structural Equation Modelling, 2025)
This study examines the comparative influence of empowerment leadership and transformational leadership behaviours on employees' psychological well-being (PWB) while considering the mediating effect of perceived organisational support. A simple random samplingtechnique was employed to gather 394 responses from the staff of Tanzanian public higher learning institutions (HLIs). The collected data was analysed using partial least squares structural equation modeling. The results indicate that empowerment and transformational leadership behaviours positively and significantly improve PWB, with perceived organizational support serving as a partial mediator. To enhance PWB, HLIs should support empowerment and transformational leadership behaviours by inspiring and motivating employees and giving them authority in decision-making. Furthermore, HLIs should enhance perceived organisational support by implementing clear rules and procedures as well as demonstrating employee value and appreciation. This study uniquely examines the effects of empowerment and transformational leadership behaviours in relation to PWB. In particular, the study identifies perceived organisational support as a mediator variable in this model, a dimension notthoroughly investigated in prior research.